Trust, privacy, and security in digital business : 13th International Conference, TrustBus 2016, Porto, Portugal, September 7-8, 2016. Proceedings /: 13th International Conference, TrustBus 2016, Porto, Portugal, September 7-8, 2016. Proceedings. (2016) - Unknown
No abstract available